Physicochemical, Nutritional, and Structural Characterization of a Novel Meat-Based Hummus - Meena Goswami; Rishav Kumar; Xin M. Teng; Ravi Jadeja; Darren Scott; Morgan Pfeiffer; Gretchen G. Mafi; Vikas Pathak; Ranjith Ramanathan (Foods)
The objective was to characterize physicochemical, nutritional, and structural properties of a novel meat-based hummus. This product was created by substituting 50% of chickpea paste with mutton. The meat-based hummus contained 0.4% sodium acid sulfate as an antimicrobial agent. The pH values of traditional hummus were greater than those of the meat-based hummus. There was no significant difference in day 0 total plate count between plant- and meat-based hummus; however, the total plate count on day 7 was significantly (p < 0.05) lower in the meat-based hummus than plant-based hummus due to antimicrobial addition. Instrumental color analysis showed greater lightness (L* values) and yellowness values for traditional hummus compared to the meat-based hummus. The meat-based hummus had 66% greater protein than traditional hummus. Scanning electron microscopy revealed a porous, gel-like structure in plant-based hummus, while meat-based hummus showed a dense, fibrous network. The flavor, creaminess, grain properties, and mouth coating scores of meat-based hummus were greater than those of traditional chickpea hummus. The study indicated that meat-based hummus can be developed by incorporating 50% cooked minced mutton. Creating innovative meat-based products like meat hummus offers the benefits of both plant-based and animal-based diets, making it a good option for flexitarians.